ACADEMIC MANAGEMENT COMPETENCIES OF ADMINISTRATORS AFFECTING THE EFFECTIVENESS OF SARASAS AFFILIATED SCHOOLS - Lobrod , Panisara; Pechrpuang, Sopon (Journal of MCU Nakhondhat, 2023)
The purpose of this research were to study 1) the Academic Management Competencies of Administrators in Sarasas Affiliated Schools. 2) the Effectiveness of Sarasas Affiliated Schools 3) the Academic Management Competencies of Administrators Affecting the Effectiveness of Sarasas Affiliated Schools. Population is teacher 7,869 person whom working for Sarasas Affiliated Schools, the sample were 367 person obtained by Stratified Random Sampling then use simple random sampling. The questionnaires was use to collect data and has reliability statistics is 0.97 of Cronbach’s Alpha for whole issue. The statistics used to analyze the data were mean, standard deviation and stepwise multiple regression analysis. The finding were 1) The Academic Management Competencies of Administrators of Sarasas Affiliated Schools Overall and each aspect was at a high level. Sorted from the highest average to the lowest, including supervision of learning management. curriculum development and learning management, and promoting research to improve the quality of learning management. 2) The Effectiveness of Sarasas Affiliated Schools Overall and each aspect was at a high level. Sort from highest average to lowest as follows. Ability to modify and develop schools ability to solve problems within school. The ability to develop students to have a positive attitude and the ability to produce students with high academic achievement. 3) The Academic Management Competencies of Administrators Affecting the Effectiveness of Sarasas Affiliated Schools and variable was selected into the equation was curriculum development. Learning Management supervision of learning management and promotion of research to improve the quality of learning management, respectively, with a statistical significance of .05 and were able to jointly predict the effectiveness of Sarasas Affiliated Schools by 76.30 percent.